2021
DOI: 10.1177/08903344211039182
|View full text |Cite|
|
Sign up to set email alerts
|

Baby Friendly Hospital Initiative Breastfeeding Outcomes in Mothers with COVID-19 Infection During the First Weeks of the Pandemic in Spain

Abstract: Background: Adherence to the Ten Steps of the Baby-Friendly Hospital Initiative has been shown to have a protective role for the initiation and maintenance of breastfeeding. Research Aims: (1) To determine the breastfeeding rate during the first 6 months of life in children of mothers diagnosed with COVID-19 infection at the time of birth; and (2) to assess the possible influence of being born in a center with Baby-Friendly Hospital Initiative accreditation. Methods: This was a two-group comparative longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…However, given the small number of similar studies, we think that our results may still make a useful contribution. The low exclusive breastfeeding rate among the mothers with COVID‐19 in our study (50.0%) confirms the results of other studies 19,20 . Breastfeeding has always been indicated in our hospital, but, having seen the findings by Indrio et al, 21 we hypothesised that the restrictions on skin‐to‐skin contact and rooming‐in may have contributed to reduce breastfeeding in this group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, given the small number of similar studies, we think that our results may still make a useful contribution. The low exclusive breastfeeding rate among the mothers with COVID‐19 in our study (50.0%) confirms the results of other studies 19,20 . Breastfeeding has always been indicated in our hospital, but, having seen the findings by Indrio et al, 21 we hypothesised that the restrictions on skin‐to‐skin contact and rooming‐in may have contributed to reduce breastfeeding in this group.…”
Section: Discussionsupporting
confidence: 88%
“…The low exclusive breastfeeding rate among the mothers with COVID-19 in our study (50.0%) confirms the results of other studies. 19,20 Breastfeeding has always been indicated in our hospital, but, having seen the findings by Indrio et al, 21 we hypothesised that the restrictions on skin-to-skin contact and rooming-in may have contributed to reduce breastfeeding in this group. The low rates for these practices were similar to those found in other studies.…”
Section: Discussionmentioning
confidence: 79%
“…To date, in these types of hospitals, there is not enough evidence about the impact that a maternal COVID-19 infection at the time of the birth could have, even more so when the application of measures such as immediate skin-to-skin care or rooming-in have been reinstated after the initial controversy [ 5 , 6 ]. In a study conducted in the first weeks of the pandemic in Spain [ 14 ], the rates of exclusive breastfeeding upon discharge for the newborns of mothers with a COVID-19 infection were 49.1% in BFHI-accredited hospitals versus 35.3% in non-accredited hospitals; figures that are lower than those obtained in our study due, primarily, to the initial difficulty found in adapting the perinatal care measures recommended by the WHO [ 7 ]. Likewise, in three BFHI-accredited hospitals in the first weeks of the pandemic, Popofsky et al observed a reduction in the rates of exclusive breastfeeding in those mothers who had a COVID-19 infection [ 25 ].…”
Section: Discussioncontrasting
confidence: 78%
“…During the first waves of the pandemic and due, on many occasions, to the pressure on healthcare and the reorganization of hospital activities, it became more difficult to comply with perinatal care protocols, even in BFHI-accredited hospital centers [ 14 , 15 ]. This resulted in a reduction in the rates of exclusive breastfeeding upon discharge with figures below the requirements established by the BFHI compared to historical cohorts (prior to COVID-19) [ 14 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation